Electrical properties of Brain Tissues of Irradiated Rats within (1x10-4 - 5) MHz - Ahmed M Elhaj (The Libyan Journal of Science, 2022)
X-ray radiation exposure to brain tissues can cause a serious damage, and therefore, studying the radiation effects becomes essential. In this study, thirty albino male rats were divided into two groups, control (6 rats), and 24 rats that their whole body were subjected to 4 Gy radiation. The irradiated rats then sacrificed (4 rats each) in different periods 1, 4, 9, 16, 23, 30 days. The electrical impedance, conductivity and relative permittivity of the brain tissues are calculated in frequency range 0.0001MHz and 5 MHz. Additional measurements at selected low, intermediate and high frequency are considered. The results show significant differences between the control and irradiated tissues. This occurs highly in brain conductivity and less on the relative permittivity. The changes in the electrical properties due to whole body exposure indicate that 4Gy of X-irradiation has affected brain cells more rapidly at 9 days and did not induce acute and immediate cell death, so they gradually recover after weeks later.